Pembelajaran Membaca dan Menulis Melalui Penggunaan Bahasa Ibu di SDN 153 Rejang Lebong - Kartika, Yeni; Botifar, Maria; Putra, Muksal Mina (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
Student learning at this level is very important for reading and writing skills which are the driving force for research. Need for learning to read and write to students. are two abilities that must be taught. Lower grade students who learn in their native language usually show better learning outcomes. Purpose of this study was to identify barriers and challenges associated with reading and writing learning as well as the process of learning to read and write through mother tongue. Qualitative method descriptive instruments used interviews, observation, documentation. The results of the study, the first step in learning to read the mother tongue is to introduce letters of the alphabet, string words, read aloud, read sentences, read self-identity, and distinguish letters of the alphabet. Write alphabets, words, sentences, write self-identity, write the difference between capital and lowercase letters. Through asking and answering and interacting with friends, students understand what the teacher teaches, difficulty understanding letters, intellectual and environmental factors.